P287 Effect of closely repeated cathodal transcranial direct current stimulations. Issue 3 (March 2017) - Uncini, A.; Zappasodi, F.; Musumeci, G.; Navarra, R.; Caulo, M.; Di Lazzaro, V.
Abstract : Question: Transcranial direct current stimulation (tDCS) is usually employed in humans with intensity up to 2 mA, duration up to 20 min, once a day for maximum two weeks. The duration and strength of the after-effects of tDCS depend on intensity, duration and repetition. We previously showed that in the rat cathodal tDCS with high, although still in the safety limits, current and charge density (2.83 mA/cm 2 and 25470 C/m 2 ) applied 12 times in 6 h did not cause microscopic damage at histology. Aim of this work is investigate the effects and safety of closely repeated cathodal tDCS in humans. Methods: Eight right handed healthy volunteers (6 males, age: 20–42 years) received within 24 h 5 cathodal tDCS by a 70 cm 2 electrode centered over the cortical representation of the left first interosseous dorsalis (intensity 2 mA with current density 0, 0286 mA/cm 2, duration 20 min with charge density 342.8 C/m 2, total charge density for 5 stimulations 1714.2 C/m2 ) and by a return electrode placed on the ipsilateral shoulder. 3T MRI (volumetry, spectroscopy, diffusion and susceptibility weighted images), visual reaction time, Flanker test, N-back test and verbal fluency test were done at baseline and after 3 and 5 stimulations. MEPs after TMS were recorded in the contralateral FDI. Results: Four hours after the second stimulation MEP amplitude was significantly reduced compared to baseline. MRI showed no modifications of the baseline images after 3 and 5 stimulations and in particular no evidence of ischemia, vasogenic edema, hemorrhage or cortical swelling. The Flanker and N-back tests showed an improvement in the mean response time and percentage of correct responses after 5 stimulations compared to baseline. Visual reaction time and verbal fluency did not change. All subjects tolerated well the procedure reporting only a mild stinging sensation under the cephalic electrode during the stimulation. No lesion or redness of the scalp or shoulder skin developed. Conclusion: We confirm in humans that an intensive protocol with closely repeated cathodal tDCS is safe and can be used in the attempt to obtain stronger and long lasting effects for clinical purposes.